2013
DOI: 10.1007/s00784-013-1160-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of ozone and fluoride varnish application on occlusal caries in primary molars: a 12-month study

Abstract: Neither ozone nor fluoride varnish treatments stopped the progression of caries in cavitated lesions. In low and medium caries risk children, non-cavitated lesions following both treatments showed slight or no progression. The use of ozone or fluoride varnish treatments in this regime as caries preventive method, added to the daily use of fluoridated toothpaste, to arrest caries progression in primary molars must therefore be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
0
27
0
4
Order By: Relevance
“…Numerous studies have been focused on the double effect of fluoride on bone and tooth formation. Although chronic accumulation of fluoride can lead to skeletal and dental fluorosis, low‐level fluoride is normally used to treat bone disorders and prevent dental caries (Johansson et al, ; Morabito et al, ). Recent years, some studies found that low concentrations of fluoride can induce the proliferation and mineralization of bone marrow mesenchymal stem cells and periodontal ligament cells (Guida et al, ; K. Q. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been focused on the double effect of fluoride on bone and tooth formation. Although chronic accumulation of fluoride can lead to skeletal and dental fluorosis, low‐level fluoride is normally used to treat bone disorders and prevent dental caries (Johansson et al, ; Morabito et al, ). Recent years, some studies found that low concentrations of fluoride can induce the proliferation and mineralization of bone marrow mesenchymal stem cells and periodontal ligament cells (Guida et al, ; K. Q. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that knocking down ATG5 blocked NaF-induced ALP activity (Figure 4d). PCR assay for mRNA expression and Western blot analysis for protein expression of osteo/odontogenesis-related molecules showed that autophagy inhibition by knocking down ATG5 blocked osteo/odontogenic differentiation of SCAPs (Figure 4e used to treat bone disorders and prevent dental caries (Johansson et al, 2014;Morabito et al, 2003). Recent years, some studies found that low concentrations of fluoride can induce the proliferation and mineralization of bone marrow mesenchymal stem cells and periodontal ligament cells (Guida et al, 2010;K.…”
Section: Knocking Down Atg5 Suppressed Naf-induced Differentiation mentioning
confidence: 99%
“…Ir pieņemts, ka jēdziena "remineralizācija" sinonīms ir "kariesa progresēšanas apturēšana" (Pretty & Ellwood, 2013). Tāpēc ir svarīgi pēc iespējas agrīnāk identificēt sākotnējos emaljas bojājumus un novērst to attīstību, un tas tiek uzskatīts par daudz efektīvāku līdzekli nekā plombēšana (Johansson et al, 2014 (Polydorou et al, 2012). Viena no kariesa profilakses stratēģijām ir samazināt kariesu izraisošo mikroorganismu skaitu zobu aplikumā, tādējādi novēršot kariesa veidošanos un attīstību (Johansson et al, 2009).…”
Section: Ievadsunclassified
“…Johansson apliecina, ka ozona un fluorīdus saturošas lakas kombinācija ir ieteicams līdzeklis kariesa profilaksē (Johansson et al, 2014 Izvērtējot iegūtos rezultātus, secinājām, ka ozons, fluorīdu laka un silanti ir vienlīdz efektīvi līdzekļi premolāru kariesa profilaksē.…”
Section: Ozona Ietekme Uz Zoba Audu Mineralizāciju Premolāru Kariesa Profilaksēunclassified
“…Thanks to modern prevention methods, which allow treatment and stopping of caries at an early stage of its development, it is possible to achieve significant reduction in intensity of caries (Marthaler, 2004;Neuhaus et al, 2009). It is important to identify as early as possible the initial enamel lesions to prevent their progression, and it is considered to be more effective means than filling (Johansson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%